Dielectric properties of flash spark plasma sintered BaTiO3 and CaCu3Ti4O12. (December 2019) - Manière, Charles; Riquet, Guillaume; Marinel, Sylvain
Abstract: Flash sintering is an approach allowing reducing the sintering time to mere seconds. To improve the microstructures and the properties of flash sintered specimens, this process has been successfully adapted to pressure assisted sintering such as the spark plasma sintering. This work is the exploration of the potential of this ultra-rapid sintering process for the improvement of the dielectric properties of well-known materials such as BaTiO3 and CaCu3 Ti4 O12 . In particular, we focus on the potential improvement of the dielectric loss, colossal permittivity and microstructures of these materials after 20 s sintering and annealing. Graphical abstract: FlashSPS of BaTiO3 and CaCu3 Ti4 O12, microstructure analysis and dielectric properties.Unlabelled Image Highlights: FlashSPS of BaTiO3 and CaCu3 Ti4 O12 Flash sintered microstructure, phase preservation/decomposition Improvement of the dielectric properties by flashSPS